Metode Simak-Berantai Dalam Meningkatkan Kualitas Pembelajaran Menyimak Pada Mahasiswa PBSI Angkatan 2021B IKIP Budi Utomo - Artifa Sorraya; Luly Zahrotul Lutfiyah; Yana Yana (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2022)
The method in improving the quality of listening learning is the chain-listening method. The chain-listed method is where students os students shisper something that is in accordance with the learning material to a learner who has lined up neatly. Student or students whisper the message to the second student. the second student whispered to the third student, and the same amounted to the last student. The last student mentions the message in a clear voice in front of the class. the facilitator or lecturer corrects and evaluates whether the message really reaches the last student or not and for students it can improve the quality of listening learning through the chain-listen method. The purpose of this studay was to determine the improvement of listening skills through the chain-listening method in PBSI students batch 2021B, Ikip Budi Utomo. This type of research is classroom action research which consists of two cycles. The subjects in this studay were PBSI students batch 2021B. Dsta analysis techniques in this study consisted of qualitative and quantitative data. Qualititative data obtained through observation and quantitative data obtained through observation and quantitative data obtained through test results in improving the qualitaty of listening learning.